Synthesis, electrochemistry, spectroelectrochemistry and electropolymerization of metal-free and metallophthalocyanines - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Metal-free 4 and metallophthalocyanine complexes 5-7 (MPcs, M = Ni, Co, Cu) substituted with the electropolymerizable (2{2-[3-(dimethylamino)phenoxy]ethoxy}ethoxy) group have been synthesized and their structure have been identified by IR, H-1 and C-13 NMR, mass and UV-Vis spectroscopy techniques. The electrochemical characterization of the phthalocyanines sustained the submitted structures of the complexes, since the half wave peak potentials of the redox processes are in harmony with the common electrochemical behavior of MPcs. CoPc gives a metal based reduction process in addition to the ligand based electron transfer processes, which enrich the possible usage of the complex in various electrochemical technologies. All the complexes were coated on the working electrode with an oxidative electopolymerization process during the anodic potential scans. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Cobalt; Synthesis; Electropolymerization; Electrochemistry; SUBSTITUTED PHTHALOCYANINES; INDIUM PHTHALOCYANINES; COBALT PHTHALOCYANINES; NICKEL PHTHALOCYANINE; PERIPHERAL POSITIONS; CATALYTIC-ACTIVITY; FILMS; MANGANESE; COMPLEXES; BEHAVIOR